The effect of obesity, macronutrients, fasting and nutritional status on drug-metabolizing cytochrome P450s: a systematic review of current evidence on human studies - Zarezadeh, Meysam; Saedisomeolia, Ahmad; Shekarabi, Mahoor; Khorshidi, Masoud; Emami, Mohammad Reza; Müller, Daniel J. (European journal of nutrition, 2021)
Background Cytochrome P450s (CYPs) are a class of hemoproteins involved in drug metabolism. It has been reported that body composition, proportion of dietary macronutrients, fasting and nutritional status can interfere with the activity of drug-metabolizing CYPs. Objectives The present systematic review was conducted to summarize the effect of obesity, weight reduction, macronutrients, fasting and malnutrition on the CYP-mediated drug metabolism. Methods PubMed (Medline), Scopus, Embase and Cochrane Library databases and Google Scholar were searched up to June 2020 to obtain relevant studies. The PRISMA guidelines were employed during all steps. Two reviewers independently extracted the information from the included studies. Studies investigating CYPs activity directly or indirectly through pharmacokinetics of probe drugs, were included. Increase in clearance (CL) or decrease in elimination half-life ( t ½) and area under the curve (AUC) of probe drugs were considered as increase in CYPs activity. Results A total of 6545 articles were obtained through searching databases among which 69 studies with 126 datasets fully met the inclusion criteria. The results indicated that obesity might decrease the activity of CYP3A4/5, CYP1A2 and CYP2C9 and increase the activity of CYP2E1. The effect of obesity on CYP2D6 is controversial. Also, weight loss increased CYP3A4 activity. Moreover, CYP1A2 activity was decreased by high carbohydrate diet, increased by high protein diet and fasting and unchanged by malnutrition. The activity of CYP2C19 was less susceptible to alterations compared to other CYPs. Conclusion The activity of drug-metabolizing CYPs are altered by body composition, dietary intake and nutritional status. This relationship might contribute to drug toxicity or reduce treatment efficacy and influence cost-effectiveness of medical care.